Elita a zagadnienie władzy politycznej - Żyromski, Marek (Wydział Prawa i Administracji UAM, 1989)
The author tries to prove the significance of including the factor of power in building theories of elites. It turns out that in many approaches the elite has been defined mostly and exclusively in terms of political power (Pareto, Mosca, Lasswell, Mills). Such an attitude followed from the adoption of „a priori" assumptions about the universality of dividing societies into those who govern and those governed (Italian scholars) and from empirical studies (especially Mills). Also the sociologists who stressed a highly diversified character of contemporary societies point to a great role of factors of a political character (Mannheim, Keller). Political power is not only an important criterion of stratifying the society but also of distinguishing the elite. Defining power appears to be very difficult. At present, with more and more diversified social structures, it is more difficult than several decades ago to indicate persons or groups who really (not nominally) are in authority.
The elits and the question of political power